A simple figure of merit for evaluating interleaver depth for the land-mobile satellite channel. - Rice, M.
The selection of interleaver depth for the land-mobile satellite channel is investigated by analyzing the performance of convolutionally encoded BPSK and DPSK over a frequency-nonselective correlated Ricean fading channel. By extending previous analyses of partially interleaved convolutional codes over such channels, a new figure of merit-which is a function of the channel correlation function-is identified. Simulation results for the first-order Butterworth, Jakes (1974), and Divsalar (1991) fading spectra are presented which demonstrate the applicability of the figure of merit as an aid in interleaver design. The figure of merit also tracks the nonmonotonic, or quasi-oscillatory, behavior of the decoded bit error rate with increasing interleaver depths in those situations where this occurs
Keywords: Divsalar fading spectra; Jakes fading spectra; Channel correlation function; Convolutionally encoded BPSK; Convolutionally encoded DPSK; Correlated Ricean fading channel; Decoded bit error rate; Figure of merit; First-order Butterworth fading spectra; Frequency-nonselective fading channel; Interleaver depth; Land-mobile satellite channel; Nonmonotonic behavior tracking; Partially interleaved convolutional codes; Performance analysis; Quasi-oscillatory behavior tracking; Simulation results